Review of Joakim Radkau's Wood: A History - Seirinidou, Vaso (Historein, 2013)
Review of Joachim Radkau’s Wood gets us back to basics, to the fundamental materials of human existence and the fundamental concerns of human societies. The book is about the interaction between wood and humans throughout history. It is a “tribute” to a material that although it has marked human culture from the Stone Age to the early stages of the industrialization, it has barely been transformed into a subject of historical narrative. However, the importance of Wood lies not mainly in the historical rehabilitation of a neglected material, but rather in the historisation of the actual global concern about the ways societies deal with limited resources